Comparison Between Posterior Cartilage Window and Aspiration and Quilting Technique in Treatment of Pseudocyst of Pinna - Koirala, K; Rai, S; Chhetri, S; Shah, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 10-12 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6795